BADDELEYITE: A PROMISING GEOCHRONOMETER FOR ALKALINE AND BASIC MAGMATISM - Bayanova T.B. (My University, 2006)
The paper is devoted to the history of the discovery, petrological and mineralogical characterization, and U-Pb dating of baddeleyite ZrO2, which was separated from various Archean, Proterozoic, and Paleozoic rocks from Fennoscandia. The morphology of this mineral and its U-Pb age values were examined in the Archean carbonatites (2613 ± 18 Ma) of Siilinjarvi, Finland, and gabbronorite dikes (2738 ± 6 Ma) at the Kirovogorskoe deposit. U-Pb isochrons are reported for the baddeleyite-zircon pair obtained from the gabbronorites and anorthosites of the Proterozoic pyroxenite-gabbronorite-anorthosite association. The U-Pb baddeleyite dates for the early gabbronorite phase (2.5 Ga) and for a gabbronorite dike (late phase, 2.4 Ga) suggest that the basic magmatism evolved over a long time period (100 m.y.) in the Proterozoic. U-Pb dates are also reported for baddeleyite from the Paleozoic carbonatites of Kovdor, Sebljarv, and Vuorijarvi.